Development of powder flow model of laser solid forming by analysis method. Issue 5 (February 2016) - Tan, Hua; Zhang, Fengying; Fu, Xin; Meng, Jian; Hu, Guang; Fan, Wei; Huang, Weidong
Abstract Laser solid forming (LSF) is a promising additive manufacturing technology. Powder flow plays an important role during the LSF process. In this study, based on the flux balance and the introduction of specific parameters, a practical model was developed to simulate the powder flow of the discontinuous coaxial nozzle with four symmetrical tips. The observation experiments of powder feed process were carried out, and the specific powder flow parameters and the powder flow feed behavior were obtained. It can be found that the simulations of the powder flow agreed well with the experimental measurements due to the introduction of specific powder flow parameters. In addition, it can be also found that the peak value of the powder mass concentration is above the theoretical focus position of the powder flow. Further, the analysis model was used for the calculation of the deposition layer height. It was showed that the deposition layer size varied significantly with the distance between the deposited surface and the nozzle exit plane due to the variation of the powder mass concentration. It can be concluded that the analysis model of powder flow has potential use for building the deposition layer formation model to analyze the LSF process.